2016
DOI: 10.4238/gmr.15038376
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ganglioside GM1 and neural growth factor on neural stem cell proliferation and differentiation

Abstract: ABSTRACT. Neurogenesis, recovery from nerve injury, neurodegeneration, and Parkinson's disease affect people's health, yet the underlying molecular mechanisms remain elusive. Here, we investigated the effect of ganglioside GM1 and neural growth factor (NGF) on neural stem cell (NSC) proliferation and differentiation in vitro to provide a scientific basis for comprehensive treatment of nervous system diseases via NSC application. As widely applied methods of relatively high accuracy, cell counts and 3-(4,5-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The dose-dependent effects of GM1 and GD3, for instance, are most intriguing (Itokazu et al 2013;Wang et al 2016). It is already known that NSCs express GD3 as the most abundant ganglioside (Nakatani et al 2010), and co-localize with EGFR regulating cell proliferation (Itokazu et al 2013) (Fig.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The dose-dependent effects of GM1 and GD3, for instance, are most intriguing (Itokazu et al 2013;Wang et al 2016). It is already known that NSCs express GD3 as the most abundant ganglioside (Nakatani et al 2010), and co-localize with EGFR regulating cell proliferation (Itokazu et al 2013) (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…; Wang et al . ). EGFR interaction with the Nā€linked GlcNAc oligosaccharides portion of GM3 (NeuAcĪ±2ā€3GalĪ²1ā€4GlcĪ²1ā€1ā€²Cer), in a cis fashion (Regina Todeschini and Hakomori ), which has a negative impact on the EGFR tyrosine kinase (Hanai et al .…”
Section: Gsls In Neural Stem Cellsmentioning
confidence: 97%
See 1 more Smart Citation
“…Over the past few years, it was found that the neuroprotective drug monosialotetrahexosyl ganglioside (GM1) promotes growth and repair the neurological impairment. As reported, the exogenous GM1 has been used to promote the nervous system cell regeneration and synapse formation ( 7 , 8 ). However, the role of GM1 in patients with severe ischemic brain injury is rarely reported.…”
Section: Introductionmentioning
confidence: 95%
“…1 2 Previous reviews confirm an essential role of GA in brain structure and function. [3][4][5] They are also reported to provide protection from inflammation, neurodegeneration, 6 7 apoptosis and tumours, 8 9 to accelerate neural development of the newborn [10][11][12][13] and to contribute to learning and memory. [14][15][16] In addition, decreased levels of GA contribute to The CLIMB (Complex Lipids In Mothers and Babies) study: protocol for a multicentre, three-group, parallel randomised controlled trial to investigate the effect of supplementation of complex lipids in pregnancy, on maternal ganglioside status and subsequent cognitive outcomes in the offspring Shuai Huang, 1,2 Ting-Ting Mo, 3 Tom Norris, 4 Si Sun, 3 Ting Zhang, 1,2 Ting-Li Han, 2,5 Angela Rowan, 6 Yin-Yin Xia, 3 Hua Zhang, 1,2 Hong-Bo Qi, 1,2 Philip N Baker 2,5,7 Mothers and Babies) study is the first large clinical trial to perform interventions with complex milk lipids (CML) during pregnancy in humans.…”
Section: Introductionmentioning
confidence: 99%